2018
DOI: 10.1038/s41598-018-28627-z
|View full text |Cite
|
Sign up to set email alerts
|

Indole-3-acetic-acid-induced phenotypic plasticity in Desmodesmus algae

Abstract: Phenotypic plasticity is the ability of a single genotype of an organism to exhibit variable phenotypes in response to fluctuating environments. It plays a crucial role in their evolutionary success. In natural environments, the importance of interactions between microalgae and other microorganisms is generally well appreciated, but the effects of these interactions on algal phenotypic plasticity has not been investigated. In this study, it revealed that indole-3-acetic acid (IAA), the most common naturally oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 46 publications
2
24
0
Order By: Relevance
“…We found that the algal strains we assayed here have different response patterns to the external IAA. In this study and our previous study, we found that when IAA concentration increased, the mean number of cells per particle of some Desmodesmus species decreased (Chung et al, 2018). The surface-to-volume ratios of the unicells was larger than the colony cells in microalgae.…”
Section: Notessupporting
confidence: 66%
See 4 more Smart Citations
“…We found that the algal strains we assayed here have different response patterns to the external IAA. In this study and our previous study, we found that when IAA concentration increased, the mean number of cells per particle of some Desmodesmus species decreased (Chung et al, 2018). The surface-to-volume ratios of the unicells was larger than the colony cells in microalgae.…”
Section: Notessupporting
confidence: 66%
“…We also demonstrated that these unicells exhibited a lower tendency to sedimentation than did large cells and that shrinkage may facilitate nutrient uptake and light capture (Chung et al, 2018). However, whether other coenobial algal species of Desmodesmus use the same strategy to overcome stress remains unknown.…”
Section: Introductionmentioning
confidence: 79%
See 3 more Smart Citations